New insights on unique therapeutic potentialities of prostacyclin and prostacyclin synthase. (June 2020) - Khan, M.I.; Batool, F.; Kalsoom, F.; Ali, R.; Li, F.; Wang, J.; Haider, Z.; Bilal, M.; Rajput, M.U.; Kazmi, A.; Qiu, B.
Abstract: Prostacyclin (PGI2) synthase (PGIS) is not only crucial for vascular regulation but also important in driving other activities. Many researchers have reported its significance and highlighted on the critical role of PGIS in terms of health and disease. Besides activating vascular regulation, it inhibits platelet aggregation, prevents the metastasis of cancer, mediates inflammatory response, directly or indirectly regulates the apoptosis, which has been reported to be altered in several diseases. Inadequate expression of this enzyme results in disorders of clotting mechanism, cardiac problems, hypertension, and even is a prognostic factor for cancer patients' survival. Down-regulation in several types of cancers, genetic modifications or mutation of the PGIS gene has been associated with increased risk of thrombosis, stroke, myocardial infarction, and many more complications. Genetic transcription profiling of pulmonary artery hypertensive patients disclosed the diversity of PGIS promoter sequence polymorphisms and discovered the relationship of promoter sequence variants and their expression. Genetically engineered PGIS proved to be very useful for the long-term maintenance and stability of cardiac treatment cell lines. Transfection of the PGIS gene into the liver cells of diabetic rats explained a new direction for the treatment of pulmonary hypertension. Even though significant work has been reported in several studies, no comprehensive review of recent potential insights on PGIS is available in the literature. In this review, we focus on the recent advances on PGI2 and PGIS expression and therapeutic applications in different diseases. Highlights: Pharmacobiochemical and physiological aspects of prostacyclin are discussed. PGIS expression in different diseases are deliberated. Pathological Therapeutic potentialities of prostacyclin and prostacyclin synthase are discussed.